Comparison and correlation of asphalt binder and mixture cracking parameters incorporating the aging effect. (27th September 2021) - Zhang, Runhua; Sias, Jo E.; Dave, Eshan V.
Highlights: Binder parameters evaluated in this research correlate well with each other. Binder parameters generally correlate well with mixture rheological and fracture parameters in context of various aging conditions, while mixture fatigue parameters only show a good relationship with binder fatigue parameters. The overall good correlations between binder and mixture cracking parameters by incorporating aging effects support previous research indicating that binders play a significant role in the cracking properties of asphalt mixtures. Comparing various binder/mixture parameters, the correlations typically improve with the increase of aging conditions, this is especially true for parameters that showed weak correlations at STA condition. Abstract: Cracking is one of the primary distresses in asphalt pavements, and aging can significantly affect the cracking properties of asphalt material. The primary objective of this study is to investigate comparisons and correlations between binder and mixture cracking property parameters subjected to different aging conditions, and further evaluate how these relationships would change with aging. Nine plant produced mixtures are conditioned following various conditioning protocols, and the corresponding binders are extracted and recovered from those mixtures. Mixture properties are measured from Complex Modulus (E*), Direct Tension Cyclic Fatigue (DTCF), Semi Circular Bending (SCB) and Disk-shaped Compact Tension (DCT) tests. Binder tests include Complex Shear Modulus (G*) and the Linear Amplitude Sweep (LAS) test. The binder and mixture parameters measured include thermo-rheological parameters, fatigue indices and fracture parameters. Different statistical analysis methods including the Pearson, Kendall and Hoeffding's D analysis, and frequency curves are used to investigate the comparisons and correlations between the parameters. The results from this study indicate that while considering all the aging conditions, binder parameters evaluated generally correlate well with each other. Mixture parameters also show good correlations with the exception of the fatigue parameters. Mixture rheological and fracture parameters generally show moderate to strong correlations with all the binder parameters, while mixture fatigue parameters only show strong correlations with binder fatigue parameters. Further looking into these relationships with respect to the individual aging condition, the correlations between parameters typically are improved with increase of aging levels. In addition, the distributions of these performance parameters with aging show a close trend with change of asphalt chemical composition over time, indicating the fundamental relationship between asphalt chemistry and its engineering performance. The overall good correlations between binder and mixture parameters reinforce the concept that binders play a significant role in the cracking properties of asphalt mixtures.